Stimulated C2C12 Myotube Headspace Volatile Organic Compound Analysis - Tomos G. Rosser; Matthew A. Turner; James C. Reynolds; Neil R. W. Martin; Martin R. Lindley (Molecules)
Understanding exercise metabolism and the relationship with volatile organic compounds (VOCs) holds potential in both health care and sports performance. Exercise metabolism can be investigated using whole body exercise testing (in vivo) or through the culture and subsequent electrical pulse stimulation (EPS) of myotubes (in vitro). This research investigates the novel headspace (HS) analysis of EPS skeletal muscle myotubes. An in vitro system was built to investigate the effect of EPS on the volatile constituents in the HS above EPS skeletal muscle. The C2C12 immortalised cell line was chosen. EPS was applied to the system to induce myotube contraction. The in vitro system was applied to the analysis of VOCs using thermal desorption (TD) sampling. Samples were collected under four conditions: environmental samples (enviro), acellular media HS samples (blank), skeletal muscle myotubes without stimulation HS samples (baseline) and EPS of skeletal muscle myotube HS samples (stim). TD sampling combined with gas-chromatography mass spectrometry (GC-MS) detected two compounds that, after multivariate and univariate statistical analysis, were identified as changing due to EPS (p < 0.05). These compounds were tentatively assigned as 1,4-Dioxane-2,5-dione, 3,6-dimethyl- and 1-pentene. The former is a known lactide and the latter has been reported as a marker of oxidative stress. Further research should focus on improvements to the EPS system, including the use of more relevant cell lines, quantification of myotube contractions, and the application of targeted analysis, metabolic assays and media analysis.